Religious Commitment in the Tradition of the Ketupat Festival: An Analysis of Q.S. An’Am: 162 Among the Javanese Community in Mangga Dua Village, Serdang Bedagai - Mutya Ramadhanti; Ardiansyah Ardiansyah (Universitas Nurul Jadid, 2026)
The Hari Raya Ketupat tradition in Mangga Dua Village, Serdang Bedagai, represents a socioreligious practice that raises questions about the relationship between local culture and Islamic creed. This study aims to examine how Q.S. al-An‘ām: 162 is interpreted to legitimize and transform this tradition within the framework of Living Qur’an studies. Using a qualitative approach, data were collected through in-depth interviews with religious leaders and community members, observation of ritual practices, and textual analysis of Qur’anic verses and Hadith commentaries. The findings show three community interpretations of the ketupat tradition: theo-cultural integration, folk-conformist identity expression, and mytho-symbolic spiritual coping. Religious authorities reinterpret the principle of lillāhi rabbil ‘ālamīn to purify intention (niyyah), shifting ketupat from a myth-laden object into a collective symbol of gratitude. This process produces a hybrid legitimacy model described as “Vessel Culture, Spirit Tauhid,” where tradition functions as a sociocultural medium while theological authority remains centered on Allah SWT. This study contributes by offering an applied model of how Qur’anic interpretation can mediate tensions between culture and creed in Muslim diaspora communities. Practically, the findings support strategies for religious moderation and culturally sensitive da‘wah. Future research can apply this model to other local traditions to explore broader patterns of adaptive Islamic interpretation in multicultural societies.